2011
DOI: 10.1100/tsw.2011.30
|View full text |Cite
|
Sign up to set email alerts
|

Recognition and Treatment of BCG Failure in Bladder Cancer

Abstract: Patients with high-grade Ta, T1, or carcinoma in situ non–muscle-invasive bladder cancer (NMIBC) are at high risk for recurrence and, more importantly, progression. Thus, both the American Urological Association and European Association of Urology recommend initial intravesical treatment with bacillus Calmette-Guerin(BCG) followed by maintenance therapy for a minimum of 1 year. The complete response rate to BCG therapy in patients with high-risk NMIBC can be as high as ∼80%; however, most patients with high-ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 77 publications
0
32
0
Order By: Relevance
“…Despite the potentially curative nature of RC, many physicians and patients refrain from RC in favor of preserving bladder function. Current conservative therapeutic options for BCG failure are limited and include repeated BCG therapy . O'Donnell and Boehle reviewed previous studies and reported that 35% of patients with BCG failure achieved durable success with the addition of another BCG therapy .…”
Section: Subclassification Of Bcg Failure and The Definition Of Bcg‐umentioning
confidence: 99%
“…Despite the potentially curative nature of RC, many physicians and patients refrain from RC in favor of preserving bladder function. Current conservative therapeutic options for BCG failure are limited and include repeated BCG therapy . O'Donnell and Boehle reviewed previous studies and reported that 35% of patients with BCG failure achieved durable success with the addition of another BCG therapy .…”
Section: Subclassification Of Bcg Failure and The Definition Of Bcg‐umentioning
confidence: 99%
“…55 In tumours that do not respond to BCG anymore, conventional intravesical chemotherapy agents, such as doxorubicin, thiotepa and mitomycin, have limited activity. In addition, valrubicin, the only FDAapproved drug for BCGrefractory CIS, is only effective in <10% of patients at 2 years and none with coincident stage T1 disease.…”
Section: Options After Bcg Failurementioning
confidence: 99%
“…For example, the use of initial chemotherapy followed by BCG, the reverse version or alternating application, as well as other novel chemotherapy regimens, have been investigated in small clinical studies. 55 In addition, several original approaches using electromotive accelera tion have been investigated. Kaasinen et al 75 conducted a study in 236 patients with recurrent Ta or T1 bladder tumours.…”
Section: Options After Bcg Failurementioning
confidence: 99%
“…Treatment options for patients following recurrence of NMIBC after BCG therapy who refuse cystectomy are limited and the majority are experimental. Options include repeat BCG treatment, an alternate immunotherapy regimen, chemotherapy, or device-assisted therapy (including electromotive intravesical administration of mitomycin C [MMC] and microwave hyperthermia and administration of MMC) [6]. …”
Section: Introductionmentioning
confidence: 99%